Time‐of‐flight modulated intensity small‐angle neutron scattering measurement of the self‐diffusion constant of water. Issue 3 (27th April 2021) - Kuhn, Stephen J.; Geerits, Niels; Franz, Christian; Plomp, Jeroen; Dalgliesh, Robert M.; Parnell, Steven R.
Abstract : A measurement of the self‐diffusion of water is presented, using the high‐resolution neutron scattering technique modulated intensity small‐angle neutron scattering (MI‐SANS). This technique uses two tuned radio frequency flippers to create a modulation in the neutron intensity that can resolve dynamics on the picosecond time scale. Abstract : The modulated intensity by zero effort small‐angle neutron scattering (MI‐SANS) technique is used to measure scattering with a high energy resolution on samples normally ill‐suited for neutron resonance spin echo. The self‐diffusion constant of water is measured over a q – t range of 0.01–0.2 Å −1 and 70–500 ps. In addition to demonstrating the methodology of using time‐of‐flight MI‐SANS instruments to observe diffusion in liquids, the results support previous measurements on water performed with different methods. This polarized neutron technique simultaneously measures the intermediate scattering function for a wide range of time and length scales. Two radio frequency flippers were used in a spin‐echo setup with a 100 kHz frequency difference in order to create a high‐resolution time measurement. The results are compared with self‐diffusion measurements made by other techniques and the general applicability of MI‐SANS at a pulsed source is assessed.